Manufacturing and Crashworthiness of Fabric Reinforced Thermoplastic Composites - Striewe, Jan André; Lauter, C.; Reuter, C.; Tröster, Thomas

Innovative largescale Production Process for multilayered Sheet-Metal-FRP-Structures - Striewe, Jan André; Reuter, C.; Lauter, C.; Tröster, Thomas

CarS: Carbon Fiber Reinforced Steel for Structural Automotive Applications - Wang, Z.; Lauter, C.; Löseke, Julian; Tröster, Thomas

Neue Prototypen-Werkzeugtechnologie für Bipolarplatten und Batteriekomponenten - Hickmann, T.; Ahlers, Dominik; Tröster, Thomas (Der Stahlformenbauer)

Einsatz der Widerstandserwärmung bei hydraulischen Schneidgeräten zum Trennen von hochfesten Stahlwerkstoffen in Kraftfahrzeugen - Siewers, Bernd
Die zunehmend eingesetzten hochfesten Stähle im Automobilbau können zu schwerwiegenden Problemen bei Verkehrsunfällen führen, da hydraulische Schneidgeräte zur Befreiung von Personen an ihre mechanischen Grenzen geraten. Ein Ansatz zur Behebung dieses Problems kann die Widerstandserwärmung der zu schneidenden Werkstoffe sein. Im Rahmen dieser Dissertation wurde durch Werkstoffuntersuchungen ermittelt, dass die hochfesten Stähle einen starken Abfall der Festigkeit aufweisen, während bei denselben Temperaturen potentielle Schneidwerkstoffe deutlich höhere Festigkeiten besitzen. Das Konzept wurde schließlich in einem Funktionsmuster umgesetzt. Schneidversuche zeigten, dass durch die Widerstandserwärmung ein deutlicher Abfall der erforderlichen Schneidkraft erreicht werden konnte. Insgesamt konnte gezeigt werden, dass die Widerstandserwärmung ein vielversprechendes Konzept darstellt, um hochfeste Karosseriestähle zuverlässig und schnell zu durchtrennen und somit die Befreiung eingeschlossener Fahrzeuginsassen zu gewährleisten.
Keywords: Leichtbau; Hybridsysteme; Werkstoffe

Influences of interface and surface pretreatment on the mechanical properties of metal-CFRP hybrid structures manufactured by resin transfer moulding - Tröster, Thomas; Schaper, Mirko; Meschut, Gerson; Mahnken, Rolf; Bobbert, Mathias; Lauter, Christian; Zinn, Carolin; Wang, Zheng; Dammann, Christian (International Journal of Automotive Composites)

Intrinsische Herstellung hybrider Strukturkomponenten in einen modifizierte RTM-Prozess - Bobbert, Mathias; Dammann, C.; Wang, Z.; Zinn, C.; Mahnken, Rolf; Schaper, Mirko; Tröster, Thomas

Laserbehandlung intrinsisch gefertigter Hybride - strukturelle, mechanische und korrosive Eigenschaften - Zinn, C.; Bobbert, Mathias; Dammann, C.; Wang, Z.; Schaper, Mirko; Meschut, Gerson; Mahnken, Rolf; Tröster, Thomas

Novel Process Approach for in-situ Insertion of Functional Elements in RTM-Applications - Bobbert, Mathias; Augethaler, Florian; Wang, Zheng; Tröster, Thomas; Meschut, Gerson (Journal of Materials Science Research)
Lightweight design in vehicles leads to an increasing use of fibre-reinforced-plastics (FRP). To ensure the possibility of detachable joints in those constructions specific joining technologies have to be developed. Available technologies are not suitable for mass production or are leading to damage in the FRP. The aim of this paper is to show the possibilities and the general feasibility of a new process approach for the application of functional elements in FRP or hybrid materials during resin transfer moulding (RTM) processes. Therefore the movement of the RTM-tool-punch is utilised to produce an interlock between the splay stud and the fibres of the non-consolidated preform. This enables the application of the elements during the RTM-process. The resin infusion leads to the consolidation of the CFRP and a further fixation of the splay stud. Pull-out-tests as well as torsion tests are showing the mechanical performance of the joints.

Shear edge tests: a benchmark in investigating the influence of different surface pretreatment methods on the shear stress of intrinsically manufactured metal-CFRP hybrids - Weidenmann, Kay André; Pottmeyer, Florentin; Wang, Zheng; Tröster, Thomas; Meiners, Dieter; Zinn, Carolin; Schaper, Mirko; Gonzalez, Jonathan Serna (International Journal of Automotive Composites)

Influences of interface and surface pretreatment on the mechanical properties of metal-CFRP hybrid structures manufactured by resin transfer moulding - Tröster, Thomas; Schaper, Mirko; Meschut, Gerson; Mahnken, Rolf; Bobbert, Mathias; Lauter, Christian; Zinn, Carolin; Wang, Zheng; Dammann, Christian (International Journal of Automotive Composites)

Large-Scale Production of High-Performance Fiber-Metal-Laminates by Prepreg-Press-Technology - Lauter, Christian; Reuter, Corin; Wu, Shuang; Tröster, Thomas (International Journal of Mechanical, Aerospace, Industrial, Mechatronic and Manufacturing Engineering)

Fatigue Strength Prediction for Titanium Alloy TiAl6V4 Manufactured by Selective Laser Melting - Leuders, Stefan; Vollmer, Malte; Brenne, Florian; Tröster, Thomas; Niendorf, Thomas (Metallurgical and Materials Transactions A)

Partial hardening of new press hardenable steels - Marten, Thorsten; Block, Holger; Tröster, Thomas

Multi-axial Material Testing at High Strain Rates in High Speed Cupping Tests - Weiß Borkowski, Nathalie; Marten, Thorsten; Block, Holger; Tröster, Thomas

Bestimmung und Optimierung von Eigenspannungen in hybriden Werkstoffsystemen aus Metall und Faserverbundkunststoff (FVK) - Frantz, M.; Lauter, C.; Wang, Z.; Tröster, Thomas

Kennwertermittlung an Faserverbundkunststoffen für Crashsimulationen mit dem FE-Solver LS-Dyna - Reuter, C.; Tröster, Thomas; Lauter, C.

Fatigue life prediction for metals processed by Selective Laser Melting using finite element analyses - Reschetnik, W.; Leuders, S.; Riemer, A.; Tröster, Thomas; Richard, H. A.; Niendorf, T.

Intrinsic Manufacturing of Metal-FRP-Hybrid Structural Automotive Components by Resin Transfer Moulding - Wang, Z.; Lauter, C.; Sanitther, B.; Frantz, M.; Tröster, Thomas

Methodology for the Product Engineering of Lightweight Structures in Multi-Material Design - Lauter, C.; Wang, Z.; Tröster, Thomas; Brandis, R.; Köchling, D.

Fatigue Behaviour of a Structural Component Manufactured by Selective Laser Melting and Investment Casting - Leuders, S.; Meiners, S.; Taube, A.; Tröster, Thomas; Niendorf, T.

Material follows form follows function - Wingenbach, Nils; Tröster, Thomas

Influences of process parameters on the mechanical properties of hybrid sheet metal-FRP-composites manufactured by prepreg press technology - Lauter, C.; Wang, Z.; Koke, Isabel; Tröster, Thomas

Textile composites in the automotive industry - Abel, P.; Lauter, C.; Gries, Thomas; Tröster, Thomas (Fatigue of Textile Composites)

Intrinsische Herstellung hybrider Strukturkomponenten in einem modifizierten RTM-Prozess - Bobbert, Mathias; Dammann, C.; Wang, Z.; Zinn, C.; Mahnken, Rolf; Meschut, Gerson; Schaper, Mirko; Tröster, Thomas

Influences of process parameters on the mechanical properties of hybrid sheet metal-FRP-composites manufactured by prepreg press technology - Lauter, Christian; Wang, Zheng; Koke, Isabel; Tröster, Thomas (20th International Conference on Composite Materials, Copenhagen)

Functionally Graded Alloys Obtained by Additive Manufacturing - Niendorf, Thomas; Leuders, Stefan; Riemer, Andre; Brenne, Florian; Tröster, Thomas; Richard, Hans Albert; Schwarze, Dieter (Advanced Engineering Materials)

On the fatigue crack growth behavior in 316L stainless steel manufactured by selective laser melting - Riemer, A.; Leuders, S.; Thöne, M.; Richard, H.A.; Tröster, Thomas; Niendorf, T. (Engineering Fracture Mechanics)

Characterization of the corrosion influence on the fatigue behavior of intrinsic CFRP-steel-hybrids - Klein, M.; Hülsbusch, D.; Walther, F.; Bartsch, M.; Hausmann, J.; Frantz, M.; Lauter, C.; Tröster, Thomas

Efficient manufacturing of hybrid structures consisting of steel and CFRP with using residual heat / Effiziente Herstellung von Hybridbauteilen aus Stahl und CFK mithilfe von Restwärmeausnutzung - Frantz, M; Lauter, Christian; Tröster, Thomas; Hausmann, J.; Bartsch, M.; Hülsbusch, D; Walther, F.

Crash simulation of high strength automotive components using advanced failure models - Block, Holger; Marten, Thorsten; Tröster, Thomas

Quasistatic and crash tests of steel-CFRP hybrid pillar structures for automotive applications - Lauter, Christian; Niewel, Joerg; Tröster, Thomas (International Journal of Automotive Composites)

Entwicklung und Herstellung von Hybridbauteilen aus Metallen und Faserverbundkunststoffen für den Leichtbau im Automobil - Lauter, Christian

Crash performance of the new press hardenable steel 15MnB6 - Block, Holger; Marten, Thorsten; Weiß Borkowski, Nathalie; Tröster, Thomas

Numerical simulation of the energy absorption of fiber-reinforced plastics - Reuter, Corin; Flore, Dominik; Pöhler, Simon; Sauerland, Kim Henning; Tröster, Thomas

Mehrachsige Werkstoffprüfung bei hoher Dehnrate im Hochgeschwindigkeits-Tiefungsversuch - Weiß Borkowski, Nathalie; Marten, Thorsten; Tröster, Thomas

Selective-Laser-Melting materials under cyclic loading: Influence of process-inherent defects on the initiation and propagation of fatigue cracks - Leuders, S.; Riemer, A.; Richard, H. A.; Tröster, Thomas; Niendorf, T.

Evaluation of the effect of defects on the mechanical performance of components manufactured by selective laser melting - Leuders, S.; Tröster, Thomas; Brenne, F.; Riemer, A.; Richard, H. A.; Niendorf, T.

On the mechanical performance of structures manufactured by selective laser melting: Damage initiation and propagation - Leuders, S.; Tröster, Thomas; Riemer, A.; Richard, H. A.; Niendorf, T.

Study of the Bond Strength of a Combination Consisting of Composite Sheet and Short-Fiber Thermoplastic - Moritzer, Elmar; Budde, C.; Tröster, Thomas; Pöhler, Simon

Parametereinfluss auf die Verbundfestigkeit einer Organoblech-Kurzfaserthermoplast-Werkstoffkombination - Moritzer, Elmar; Budde, C.; Tröster, Thomas; Pöhler, Simon (Joining Plastics)

On the fatigue properties of metals manufactured by selective laser melting – The role of ductility - Leuders, Stefan; Lieneke, Tobias; Lammers, Stefan; Tröster, Thomas; Niendorf, Thomas (Journal of Materials Research)
Abstract

Highly Anisotropic Steel Processed by Selective Laser Melting - Niendorf, Thomas; Leuders, Stefan; Riemer, Andre; Richard, Hans Albert; Tröster, Thomas; Schwarze, Dieter (Metallurgical and Materials Transactions B)

Stahl-CFK-Strukturen wie Tiefziehteile fertigen - Schmidt, H. C.; Lauter, Christian (MaschinenMarkt Compositesworld)

Verhalten von lasergeschmolzenen Bauteilen aus der Titan-Aluminium-Legierung TiAl6V4 unter zyklischer Beanspruchung∗ - Riemer, Andre; Leuders, S.; Richard, Hans A.; Tröster, Thomas (Materials Testing)

Graded Lightweight Structures Through Hot Forming - Marten, Thorsten; Block, Holger; Tröster, Thomas; Gerber, Thomas; Sikora, Sascha; Lenze, Franz-Josef

Influences of Automotive Process Characteristics on Hybrid Structures - Lauter, Christian; Hochschulz, T.; Frantz, Meike; Tröster, Thomas

Curing of fibre reinforced plastics by resistance heating of sheet metal in a hybrid structure - Siewers, Bernd; Lauter, Christian; Tröster, Thomas

Crashworthiness of Hybrid Structures - Tröster, Thomas; Lauter, Christian; Reuter, C.

Recycling of Automotive Sheet Metal-Fibre Reinforced Plastic-Hybrid Structures - Siewers, Bernd; Lauter, Christian; Tröster, Thomas